Pembelajaran Bahasa Inggris untuk Anak Usia Dini melalui Pembelajaran Digital Berbasis Luring: Studi Kasus Guru Generasi Z dan Peserta Didik Generasi Alpha - Muhammad Dava Hidayatullah; Mike Siltia; Viona Aura; Adila; Uas Gna; Ria Angraini (Universitas Muhammadiyah Bengkulu, 2026)
This study aims to describe the implementation of offline digital-based English learning for children through the Course E’azy program. The activity was conducted at the Language Center of Muhammadiyah University of Bengkulu, involving 17 participants consisting of lecturers’ children and children from the surrounding community. The program was designed to provide an engaging, interactive English learning experience that aligns with the characteristics of Generation Alpha, who are highly familiar with digital technology. Generation Z, represented by student instructors, acted as facilitators responsible for preparing lesson plans, instructional materials, and creative digital-based strategies. The learning process incorporated several methods, including interactive PowerPoint slides, large-screen learning videos, illustrative images, and adapted popular games as learning media. The results show that offline digital-based learning effectively enhanced learners’ engagement, enthusiasm, and vocabulary comprehension. Furthermore, the activities improved children’s reading, writing, and speaking confidence. This study emphasizes that digital-based learning innovations, even when conducted without full internet access, remain effective in enhancing the quality of English learning for children in the Generation Alpha era.